PHENOTYPIC SCREENING OF COWPEA (VIGNA UNGUICULATA) GENOTYPES IN RESPONSE TO PARASITIC WEED ALECTRA VOGELII - Ugbaa, Macsamuel; LUCKY OMOIGUI; LATEEF BELLO (Asian Journal of Agriculture, 2020)
Abstract. Ugbaa M, Omoigui L, Bello L. 2020. Phenotypic screening of cowpea (Vigna unguiculata) genotypes in response to parasitic weed Alectra vogelii. Asian J Agric 4: 14-17. Cowpea (Vigna unguiculata (L.) Walp) production is constrained by a number of abiotic and biotic factors. Among the biotic constraints, the parasitic flowering plant Alectra vogelii Benth.is one of the most formidable limitations in the dry savannas of West and Central Africa, a region that accounts for over 64% of world production. Alectra causes yield losses estimated between 41 and 100% in susceptible cultivars. Several control measures have been suggested for the control of the parasite. These include cultural practices, application of ethylene chemicals, and host plant resistance. Among these control measures, the use of resistance cultivars appears to be the most attractive option to the resource poor farmers in sub-Saharan Africa. This study was designed to revalidate and determine the reaction status of some improved and local cowpea genotypes to Alectra vogelii. Two screening experiments using pot culture technique and arranged in a Completely Randomized Design, were carried out in the screen house. Pot culture comprised sand and topsoil mixed in a 2:1 ratio and inoculum of 5000 Alectra vogelii seeds. To enhance effective parasite seed germination, the pot culture was watered twice a day for seven (7) days before planting of test cowpea genotypes.. At 30 days after planting (DAP) A. vogelii shoots emerged from pots planted to susceptible cowpea genotypes, although some had delayed emergence up to 40 DAP. Susceptible cowpea showed leaf chlorosis, stunted growth, and partial leaf senescence. Some developed symptoms but A. vogelii shoots did not emerge. In both experiments, cowpea genotypes of B301, IT98K-573-1-1 and IT98K-205-8 were consistently resistant. They showed no attachment or emergence of the parasite. The absence of attachment on resistant cowpea genotypes suggests hyperactive mechanism of resistance to A. vogelii. This is a localized necrotic response that killed off attached parasite at the point of contact, a form of programmed cell death (PCD). This response strongly indicates dominant action in the resistance to A. vogelii in these genotypes. Resistant genotypes can be used as sources of resistance gene to develop improved resistant cowpea varieties.